Respuesta :
Step-by-step explanation:
1. 6(5)^2-1/(5)^2 = 149/25
2. 6(-5)^2-1/25 = -150/25
3. 6x^2-2/x^2
Answer:
[tex]1) \huge\boxed{ \sf f(5) = 5 \frac{24}{25} }[/tex]
[tex]2) \huge\boxed{ \sf f(-5) = 5\frac{24}{25} }[/tex]
[tex]3) \huge\boxed{\sf f(-x) = \frac{6x^2-1}{x^2} }[/tex]
Step-by-step explanation:
[tex]\displaystyle f(x) = \frac{6x^2-1}{x^2}[/tex]
For f(5):
Put x = 5
[tex]\displaystyle f(5) = \frac{6(5)^2-1}{(5)^2} \\\\f(5) = \frac{6(25)-1}{25} \\\\f(5) = \frac{150-1}{25} \\\\f(5) = \frac{149}{25} \\\\f(5) = 5 \frac{24}{25}[/tex]
For f(-5):
Put x = -5
[tex]\displaystyle f(-5) = \frac{6(-5)^2-1}{(-5)^2} \\\\f(-5) = \frac{6(25)-1}{25} \\\\f(-5) = \frac{150-1}{25} \\\\f(-5) = \frac{149}{25} \\\\f(-5) = 5\frac{24}{25}[/tex]
For f(-x):
Put x = -x
[tex]\displaystyle f(-x) =\frac{6(-x)^2-1}{(-x)^2} \\\\f(-x) = \frac{6x^2-1}{x^2} \\\\\rule[225]{225}{2}[/tex]
Hope this helped!